包含液態晶體之兆赫波段光子晶體之設計製作及光學性質研究 - 趙如蘋; PAN RU-PIN (My University, 2009)
光子晶體及金屬孔洞陣列在可見光波段之研究是一個非常熱門的課題。而兆赫波光譜技術為一新穎的研究，但可用於此波段的光學元件相當缺乏，我們將利用光子晶體及二維金屬孔洞陣列之穿透特性，設計可於室溫下操作之波導、濾波器等元件，我們也將加入液態晶體來使這些元件具有可調變的特性。由於光子晶體尺度必須與電磁波長相匹配，在可見光波段下之光子晶體及金屬孔洞陣列在製作上相當困難。在兆赫波段，因其波長在次毫米範圍，此度叫大，所以製作反而較為容易。目前我們已經測量了此波段下包含液晶(5CB)之二維金屬孔洞陣列的穿透頻譜。其結果顯示，設計及製作兆赫波段下之液晶光子晶體元件是可行的。 鑑於包含液晶之金屬孔洞陣列濾波應用的可行性，我們進一步設計並製作不同維度的光子晶體結構。研究不同的配向技術使液晶能沿著特定方向排列於光子晶體內部。研究液態晶體於不同外場(如電場及磁場)下對光子晶體之兆赫波傳播性質的影響。進一步利用液態晶體之介電異方性設計可調變之兆赫波導及濾波器。

Researches about photonic crystals (PCs) and metallic hole arrays (MHAs) in the visible range has been a field attracting many researchers attention. On the other hand, Terahertz (THz) wave is a new field with prompt potential for medical applications. The THz spectroscopic technology is a novel research but devices used in this frequency range are very rare compared to visible light. It is difficult to fabricate PCs and MHAs for the visible range, because the dimensions of these devices have to be comparable to the wavelength of light. Since the wavelength for THz waves are millimeters and sub-millimeters, THz PCs and MHAs have larger dimension and hence are much easier to fabricate. We will design the waveguides and filters by utilizing the properties of PCs and MHAs, and these devices could be used at room temperature. Immersing with liquid crystals makes these devices even more versatile. Previously, we have measured the power spectrum of liquid crystal (5CB) with 2D-MHAs in THz range. The measured results show that it is feasible to combine the liquid crystals and PC/MHA to design tunable THz devices. Base on the preliminary results about the THz filter composed of the liquid-crystal-infiltrated MHAs, we further design and fabricate the PCs with different dimensions. To align the liquid crystal with the PCs and MHAs, the traditional alignment method by rubbing becomes impossible. In this work, we also study the new liquid crystal alignment method. Particularly, the ion-beam bombardment method will be studied. Influence of liquid crystals under different external field (such as electric and magnetic field) on the propagating properties of transmitted THz wave in PCs will be studied. Furthermore, the THz waveguides and filters are also designed using the intrinsic dielectric anisotropy of liquid crystals.
Study on Fabrication and Optical Properties of Photonic Crystals Infiltrated with Liquid Crystals in Terahertz Region
Keywords: 可調式光子晶體; 液態晶體; 兆赫波; 金屬孔洞陣列; 奈米壓印; Tunable; photonic crystals; liquid crystals; terahertz wave; metallic hole arrays; and nano-inprint.